Optimization of interference coordination schemes in Device-to-Device(D2D) communication - Si Wen; Xiaoyue Zhu; Zhesheng Lin; Xin Zhang; Dacheng Yang (2012 7th International ICST Conference on Communications and Networking in China, 2012)
Device-to-Device (D2D) communication is considered to be a promising resource reuse technology for local services, to meet the system demands of higher data rates and spectrum efficiency in future networks. In order to limit severe interference between cellular links and local D2D links, previous studies mainly focus on one or two functional blocks, such as power control and resource allocation, which seems inadequate for further exploiting D2D's potential. In this paper, several interference coordination schemes, including centralized power control, resource allocation and mode selection strategy and distributed self-optimization mechanism, are proposed. Based on the proposed optimization schemes, we provide the system performance of the D2D-enabled network and analyze the impact of local service ratio and user density. Numerical results show that D2D underlay communication can increase spectrum efficiency and provide more local service opportunities compared to pure cellular communication.